PENGATURAN TINDAK PIDANA DALAM PERATURAN DAERAH PASCA DITETAPKANNYA UU NO. 1 TAHUN 2024 - TJANDRA, CHRISTIAN ALEXANDER; PUTRA, BINTANG BAYU APRILA (Fakultas Hukum Universitas Narotama, 2026)
The enactment of Law Number 1 of 2024 concerning the Criminal Code has brought fundamental changes to the criminal law system in Indonesia, including the regulation of criminal offenses in Regional Regulations (Peraturan Daerah). This research aims to examine the regulation of criminal offenses in Regional Regulations after the enactment of Law Number 1 of 2024. The changes include the elimination of imprisonment (pidana kurungan) in regional regulations, the adoption of a new fine categorization system consisting of eight categories, the obligation for all regional governments to adjust the criminal provisions in their regulations to comply with Book One of the new Criminal Code as mandated by Article 613, and the elimination of the distinction between crimes and violations. This study uses a normative legal research method with a statutory approach and a conceptual approach. The results show that regional regulations must undergo significant adjustments in terms of criminal sanctions, legal terminology, and enforcement mechanisms to remain consistent with the new national criminal law framework. Keywords: Criminal Offense, Regional Regulation, Criminal Code, Law Number 1 of 2024